Prediction of frictional pressure drop of R134a during condensation inside smooth and corrugated tubes - Dalkilic, Ahmet Selim; Cebi, Alican; Acikgoz, Ozgen; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In the present paper, in order to understand the accuracy of 38 different correlations derived by various researchers in this field, the correlations were executed for condensation frictional pressure drop. To accomplish this goal, experimental data provided from authors' previous publications encompassing 412 points for two smooth tubes, and 334 points for five corrugated tubes, have been utilized so as to compare the determined results. The experimental setup is composed of a 2.5 m double tube for horizontal configuration and smooth and corrugated tubes at the inner diameters of 0.0081 m, while the applied mass flux range spans between 709 and 1974 kg m(-2) s(-1). The average quality of vapor and saturation pressure ranges lie within 0.09 to 0.97, and 10 to 13 bar, respectively. Determining the frictional pressure drop in two-phase flows does not involve corrugated tube geometry in the calculation of friction factor, to make this available, a slight alteration that requires the replacement of a correlation with another one in the literature was suggested with regard to friction factor approach. As a result of this, it was noticed that performances of some correlations were optimized to predict the frictional pressure drop in corrugated tubes. Additionally, the most effective correlations have been selected for the horizontal double pipe heat exchanger having smooth and corrugated tubes. Finally, alteration of the condensation pressure drop with Reynolds number are presented using both experimental data and best predictive correlations.
Keywords: Condensation; Pressure drop; Two-phase multiplier; Friction; Corrugated tube; HEAT-TRANSFER COEFFICIENT; 2-PHASE FLOW PATTERN; UNIVERSAL APPROACH; AIR-WATER; MICROCHANNEL; REFRIGERANTS; CHANNELS; PIPES; R-134A; EXCHANGERS; Thermodynamics; Mechanics